Analysis of knowledge and consumer preferences in the field of organic food - Janiak, Eliza; Orzechowska-Przybyła, Kamila; Lesiów, Tomasz (Engineering Sciences And Technologies, 2016)
The development of organic foods market has been growing significantly in recent years. Polish organic foods market is quickly developing and it is considered as one of the most rapidly growing sections of the food market. The aim of the study was to analyse and assess knowledge and behaviour of chosen group (18-45 age) consumers on the organic foods market. According to the quantitative studies/survey, considerable part of the respondents (79.6%) declare trust into the organic food products. Based on the research results it can be concluded that the major part of the respondents have sufficient knowledge to purchase and consume organic food in a conscious and rational way. However, they declared a will to expand their knowledge in the ecological food field (78.6%). The respondents (81.9%) declared reading product labels and paying attention to the ingredients of the products (43.7%) and less interest to the origin of them (26.2%). For 37.9% of the respondents the most important advantages of the organic food products were beneficial effects on human health and lack of harmful additives. They pointed also at other motives of buying organic food products like taking care of own health, environment aspect and much better quality of such food
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 1 (20), s. 43-58
Keywords: eco food; organic foods; organic food market; consumer knowledge; consumer behaviour; żywność ekologiczna; żywność organiczna; rynek żywności ekologicznej; wiedza konsumentów; zachowania konsumentów